2009
DOI: 10.1007/s10571-009-9367-5
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Rat Models of Human Neurodegenerative Disorders

Abstract: The rat is a model of choice in biomedical research for over a century. Currently, the rat presents the best "functionally" characterized mammalian model system. Despite this fact, the transgenic rats have lagged behind the transgenic mice as an experimental model of human neurodegenerative disorders. The number of transgenic rat models recapitulating key pathological hallmarks of Alzheimer's disease, Huntington's disease, amyotrophic lateral sclerosis, or human tauopathies is still limited. The reason is that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 103 publications
(89 reference statements)
0
24
0
Order By: Relevance
“…This rodent exhibits many physiological and morphological characteristics similar to those of humans. Historically, neuroscientists have preferred rats to mice as model systems and, indeed, many aspects of rat pharmacology and physiology are regarded as more relevant to humans and easier to observe than in mice (Abbott 2004;Bugos et al 2009). Furthermore, rats generally exhibit a more robust capacity for learning in behavioral tasks.…”
Section: Animal Transgenic Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…This rodent exhibits many physiological and morphological characteristics similar to those of humans. Historically, neuroscientists have preferred rats to mice as model systems and, indeed, many aspects of rat pharmacology and physiology are regarded as more relevant to humans and easier to observe than in mice (Abbott 2004;Bugos et al 2009). Furthermore, rats generally exhibit a more robust capacity for learning in behavioral tasks.…”
Section: Animal Transgenic Systemsmentioning
confidence: 99%
“…Presence of nuclear staining and microaggregates early in the course of the disease. Early overt behavioral changes seen and strength of the phenotype generally correlated with the number of CAG repeats (-200) (Heng et al 2009;Levine et al 2004;Lin et al 2001;Raymond et al 2011;Shelbourne et al 1999;Wheeler et al 2000;White et al 1997 (Bugos et al 2009;Clarke et al 2007;Echeverria et al 2004;Agca et al 2008;Flood et al 2009;Folkesson et al 2007;Liu et al 2008a;Ruiz-Opazo et al 2004 of A 3-42 after cleavage (Link 1995). Expression of this human A 42 minigene in muscle cells resulted in progressive paralysis and staining of muscle cells with a human A 42 speciWc antibody revealed A 42 deposits that reacted with Congo red and thioXavin S. Ultrastructural studies, however, revealed that the deposits were intracytoplasmic rather than extracellular as are amyloid plaques found in AD (Ewald and Li 2010).…”
Section: Knock-in Mutant Htt Using Homologous Recombination In Es Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal models represent a suitable model for in vivo and in vitro studies since there are physiological characteristics similar to those of human (Bugos, Bhide and Zilka, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As far as neurodegenerative diseases are concerned, the potential of murine models is limited because of their small-sized brain and difficulty in behavioral testing [16]. On the contrary, pig models exhibit physiological and anatomical characteristics similar to human ones and particular emphasis has been placed on swine potential for modeling symptoms and phenomena of neuropsychiatric diseases [17].…”
Section: Introductionmentioning
confidence: 99%